2019
DOI: 10.1186/s13046-019-1444-0
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of CENPM promotes hepatocarcinogenesis through mutiple mechanisms

Abstract: Background: Hepatocellular carcinoma (HCC) still remains a dominating medical challenge in early diagnosis and clinical therapy. Centromere protein M (CENPM) has been proved to be over-expressed in HCC tissues, but carcinogenic mechanism of CENPM contributing to liver cancer is poorly understood. Methods: In this study, we first explored mRNA and protein levels of CENPM in HCC samples, matching adjacent non-tumor tissues and six hepatoma cell lines by polymerase chain reaction (PCR), western blotting and immun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
37
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 43 publications
(49 reference statements)
1
37
0
Order By: Relevance
“…Recently, Yu et al defined CENPM as a complement to AFP in the diagnosis of hepatocellular carcinoma ( 8 ); Xiao et al further confirmed that CENPM was highly associated with hepatocellular carcinoma progression and could be a candidate novel biomarker for hepatocellular carcinoma ( 28 ). Investigations of the underlying mechanisms of melanoma highlighted that CENPM may play an important role in the metastases of melanoma ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Yu et al defined CENPM as a complement to AFP in the diagnosis of hepatocellular carcinoma ( 8 ); Xiao et al further confirmed that CENPM was highly associated with hepatocellular carcinoma progression and could be a candidate novel biomarker for hepatocellular carcinoma ( 28 ). Investigations of the underlying mechanisms of melanoma highlighted that CENPM may play an important role in the metastases of melanoma ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…It was found that 5 genes, including NUDT1 , E2F1 , CCNE2 , MCM5 , and CENPM , had significant correlation indices with CDC45 and were upregulated in HCC tissues. Numerous studies agree that the increased expression of these 5 genes is associated with a poor prognosis and more advanced tumor stages in HCC patients [ 13 , 26 30 ]. Moreover, research showed that E2F1 regulates DNAJA1 to promote cell proliferation and metastasis by stabilizing CDC45 in colorectal cancer cell lines [ 21 ] and that silencing CCNE2 or CENPM could inhibit HCC cell growth [ 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of miR-497-5p plays an essential role in tumorigenesis. miR-497-5p has been proven to be downregulated in NSCLC, gastric cancer, colorectal cancer, ovarian cancer, renal cell carcinoma, and melanoma [88][89][90][91][92][93][94][95]. Furthermore, in vitro and in vivo studies revealed that miR-497-5p overexpression suppressed HCC cell proliferation, colony formation, and metastasis [96].…”
Section: Discussionmentioning
confidence: 99%